THEORY OF FREEDOM OF CHOICE: PRAXIS APPLICATION IN ETHICS - Romero Huamaní, Ruth Mirihan (2014)
This article aims at analyzing the theory of choice and its application to human actions. Thesis is approached from Aristotelian ethics, known as theory of happiness. Arguments more exegesis of the iconic work of the philosopher Nicomachean Ethics (EN) by relying from other works are reviewed. The purpose is to understand the proairesis the basis of desire, being the determining any human action under the thought in view of the end, which in practice subjective is required for any intentional, because due to a number of contri-butory causes of desire itself. This theory depends an understanding of freedom and its implication on other aspects such as freedom of conscience, thought and others. The methodology applied is hermeneutics, and is within the qualitative approach. This is to interpret and discuss with the author, in order to contextualize the contributions in human acts.